The Impact of Small Spinal Curves in Adolescents Who Have Not Presented to Secondary Care: A Population-Based Cohort Study. Issue 10 (May 2016) - Clark, Emma M.; Tobias, Jon H.; Fairbank, Jeremy
Abstract : Study Design: A prospective, population-based, birth cohort study. Objective: The aim of this study was to identify whether there is any hidden burden of disease associated with smaller spinal curves. Summary of Background Data: Adolescent idiopathic scoliosis is present in 3% to 5% of the general population. Large curves are associated with increased pain and reduced quality of life. However, no information is available on the impact of smaller curves, many of which do not reach secondary care. Methods: The Avon Longitudinal Study of Parents and Children (ALSPAC) recruited over 14, 000 pregnant women from the Bristol area of South-West England between 1991 and 1992 and has followed up their offspring regularly. At age 15, presence or absence of spinal curvature ≥6 degrees in the offspring was identified using the validated dual-energy X-ray absorptiometry Scoliosis Measure on 5299 participants. At age 18, a structured pain questionnaire was administered to 4083 participants. Logistic regression was used to investigate any association between presence of a spinal curve at age 15 and self-reported outcomes at age 18 years. Results: Full data were available for 3184 participants. Two hundred two (6.3%) had a spinal curve ≥6 degrees and 125 (3.9%) had a curve ≥10 degrees (median curve size of 11 degrees). About 46.3% reported aches and pains that lasted for a day or longer in the previous month. About 16.3% reported back pain. Those with spinal curves were 42% more likely to report back pain than those without (odds ratio 1.42, 95% confidence interval 1.00–2.02, P = 0.047). Those with spinal curves had more days off school and were more likely to avoid activities that caused their pain. Conclusion: Our results highlight that small scoliotic curves may be less benign than previously thought. Teenagers with small curves may not present to secondary care, but are nonetheless reporting increased pain, more days off school, and avoidance of activities. These data suggest that we should reconsider current scoliosis screening and treatment practices. Level of Evidence: 2